KOMUNIKASI NONVERBAL PADA TARI MANDAU SUKU DAYAK KALIMANTAN TENGAH: NONVERBAL COMMUNICATION IN THE MANDAU DANCE OF THE DAYAK TRIBES OF CENTRAL KALIMANTAN - Arzeti, Adelia; Aquarini, Aquarini; Rahman, Sirojul (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Abstract The purpose of the study of Nonverbal Communication in Mandau Dance of the Dayak tribe of Central Kalimantan is to understand non-verbal communication in Mandau dance of the Dayak tribe of Central Kalimantan seen from the Lasswell communication model and to find out students' understanding of non-verbal messages in Mandau dance of the Dayak tribe of Central Kalimantan. The research approach used is qualitative research with the type of phenomenology. The research instruments used interviews and documentation. The interview instrument used Laswell's communication theory. The analysis was carried out by a) procedure stage; b) Horizonalisation procedure; and c) Cluster of Meaning procedure (textural description, structural description, essence description stage; and report. The data validity test in this study was carried out by testing credibility, transferability, dependability, and confirmability. Based on the results of the research, non-verbal communication in the Mandau dance of the Dayak tribe of Central Kalimantan is seen from the Lasswell communication model. Laswell's communication aspects: (a) Who: dancers; (b) Says What: conveys messages of spirituality, courage, or balance; (c) Through What Channel (In What Channel): in mandua dance; (d) To Whom: mandau dance audience; and (e) With What Effect: allows the audience to absorb and reflect on the messages conveyed and apply an attitude of courage and perseverance. Students' understanding of non-verbal messages in the Mandau dance of the Central Kalimantan Dayak tribe is very good because students understand that the mandau dance is not just a beautiful movement. However, there is a moral message in it.